Sublimação e arte trágica grega : reflexões metapsicológicas - Campos, Thaís Becker de (2015)
Sublimation is considered one of the most enigmatic psychic mechanisms described by Freudian psychoanalysis. We propose a reflection on the metapsychology of sublimation with reference to the Greek tragic art; we have questioned to what extent the tragic expression can contribute to a deeper understanding of the sublimating work. We emphasize the acceptance of the tragic condition of the human existence as one of the necessary qualities for psychic elaboration by sublimation. Throughout this research, we highlighted the main features and historical conditions that made possible the emergence of the tragic narratives; then we propose to do a scan, throughout Freud's work, of the metapsychological basis of the psychic process of sublimation; for thus we propose a consideration on the relationship between the psychic economy involved in sublimating process and the tragic.